2004
DOI: 10.1203/01.pdr.0000111482.43827.40
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of IGF-I in Hypoxia Tolerance Using a Rat Hypoxic-Ischemic Model: Activation of Hypoxia-Inducible Factor 1α

Abstract: Hypoxia preconditioning and subsequent tolerance to hypoxia-ischemia damage is a well-known phenomenon and has significant implications in clinical medicine. In this investigation, we tested the hypothesis that the transcriptional activation of IGF-I is one of the underlying mechanisms for hypoxia-induced neuroprotection. In a rodent model of hypoxia-ischemia, hypoxia preconditioning improved neuronal survival as demonstrated by decreased hypoxia-ischemia-induced neuronal apoptosis. To study the role of IGF-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 47 publications
3
13
0
1
Order By: Relevance
“…These findings provide support of our previous study which showed that the levels of IGF-I in the systemic and ocular compartments differ possibly because of the ocular-blood barrier (16). The increase in ocular IGF-1 levels in response to JB1 treatment may be due to increased production of IGF-1 through hypoxia-induced IGF-1 transcriptional activation (17). Alternatively, the effect may be explained by accumulation of IGF-I due to binding of IGF-1R to JB1, thereby preventing IGF-I transport and uptake.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings provide support of our previous study which showed that the levels of IGF-I in the systemic and ocular compartments differ possibly because of the ocular-blood barrier (16). The increase in ocular IGF-1 levels in response to JB1 treatment may be due to increased production of IGF-1 through hypoxia-induced IGF-1 transcriptional activation (17). Alternatively, the effect may be explained by accumulation of IGF-I due to binding of IGF-1R to JB1, thereby preventing IGF-I transport and uptake.…”
Section: Discussionsupporting
confidence: 89%
“…However, longer exposure with JB1x7 had an opposite effect on IGF-1 in the ocular compartment and was not associated with exacerbated neovascularization at P21, as expected. These intriguing findings raise the possibility that a rebound increase in IGF-I levels after exposure to JB1 may have provided protection against oxidative injury and contributed to hypoxia tolerance as previously reported by Wang et al (17). In that context, the JB1x3 dosing regimen was more effective for normalization of retinal IGF-I levels and retinal vascular abnormalities seen with H/H cycling.…”
Section: Discussionsupporting
confidence: 70%
“…The increase in HIF-1␣ was detectable in both the ipsi-and contralateral hemisphere and also after hypoxia only. These findings are not surprising inasmuch as hypoxia is the crucial signal for increased expression of HIF-1␣ (23,24). Simultaneously with increased HIF-1␣ protein expression, we observed a sharp decrease in P-Akt.…”
Section: Discussionsupporting
confidence: 63%
“…Feldser et al (15) demonstrated that insulin, IGF-I, and IGF-2 induce expression of HIF-1α, which is required for expression of genes encoding IGF-2, IGFBP-2 and IGFBP-3. Recent studies further confirmed that IGF-I transcriptional activation by HIF-1α is a metabolic adaptive responses to hypoxia (38); IGF-I stimulates HIF-1α accumulation, HIF-1α nuclear translocation, and HIF-1 activity, resulting in increased VEGF expression (13,16). Given these prior observations, the possible interaction between the HIF-1α P582S polymorphism and the IGF axis observed in this study provides new evidence that the growth hormone/insulin/IGF-axis may play an important role in prostate cancer development and angiogenesis.…”
Section: Discussionmentioning
confidence: 80%